A Survey of Perceptions and Attitudes about Water Issues in Oklahoma: A Comparative Study. (11th January 2020) - Eck, Christopher J.; Wagner, Kevin L.; Chapagain, Binod; Joshi, Omkar
Abstract: Understanding people's perceptions of the environment, drinking water issues, and protecting and preserving water resources is of great importance. This study aims to assess and compare the perceptions of the general public ( n = 414), post‐secondary students ( n = 103), and water professionals ( n = 104) in Oklahoma on water issues in the state. To address these goals, a 53‐item paper questionnaire was first administered to a randomly sampled mailing list of Oklahoma residents. As a follow up to the initial survey, post‐secondary students at Oklahoma State University were sampled in addition to Oklahoma water professionals at regional conferences. Respondents ranged from 18 to over 65 years old, with all three demographics agreeing the top water priority to be clean drinking water. The majority were satisfied with their home water supply and felt it was safe to drink, while they were not sure of the quality of ground and/or surface water. Age was a key factor in information delivery and learning preferences as the older participants favored print material versus the younger demographic interest in technology. Data collected via this study provide insight into the perceptions, priorities, and learning preferences of these three populations. Despite our finding that clean water is a priority in Oklahoma, regardless of demographic, results suggest more education and outreach is needed to provide additional information regarding water in Oklahoma.